Luna Park, Surf Avenue, By Night, Coney Island, N.Y. - Underhill, Irvine (The American Art Publishing Co. New York City., 2009)
A festive painting of Coney Island at night, with automobiles and a tram travelling down the main street. Description on the back of the postcard: "Surf Avenue at night is illuminated with 1,000,000 electric lights and is the most lighted thoroughfare in the world. It is crowed with merry makers and revelers until midnight." Postcard number R-38102.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Postcards; United States; Coney Island (New York, N.Y.); Amusement parks--New York (State); Resorts--New York (State); Luna Park (New York, N.Y.); Clothing and dress--United States; Street-railroads--United States; Automobiles--United States; Carriages and carts--United States; Flags--United States; Signs and signboards--United States; Architecture--United States; Streets--United States